Direct Construction of Isomeric Benzobisoxazole-Vinylene-Linked Covalent Organic Frameworks with Distinct Photocatalytic Properties - Li, Shengxu; Ma, Rui; Xu, Shunqi; Zheng, Tianyue; Fu, Guangen; Wu, Yanling; Liao, Zhongquan; Kuang, Yongbo; Hou, Yang; Wang, Dashuai; Petkov, Petko Stoev; Simeonova, Kristina; et al. (Journal of the American Chemical Society, 2022)
Vinylene/olefin-linked two-dimensional covalent organic frameworks (v-2D-COFs) have emerged as advanced semiconducting materials with excellent in-plane conjugation, high chemical stabilities, and precisely tunable electronic structures. Exploring new linkage chemistry for the reticular construction of v-2D-COFs remains in infancy and challenging. Herein, we present a solid-state benzobisoxazole-mediated aldol polycondensation reaction for the construction of two novel isomeric benzobisoxazole-bridged v-2D-COFs (v-2D-COF-NO1 and v-2D-COF-NO2) with trans and cis configurations of benzobisoxazole. Interestingly, the isomeric benzobisoxazole linkers endow the two v-2D-COFs with distinct optoelectronic and electrochemical properties, ranging from light absorption and emission to charge-transfer properties. When employed as the photocathode, v-2D-COF-NO1 exhibits a photocurrent of up to ∼18 μA/cm2under AM 1.5G irradiation at -0.3 V vs reversible hydrogen electrode (RHE), which is twice the value of v-2D-COF-NO2 (∼9.1 μA/cm2). With Pt as a cocatalyst, v-2D-COF-NO1 demonstrates a photocatalytic hydrogen evolution rate of ∼1.97 mmol h-1g-1, also in clear contrast to that of v-2D-COF-NO2 (∼0.86 mmol h-1g-1) under identical conditions. This work demonstrates the synthesis of v-2D-COFs via benzobisoxazole-mediated aldol polycondensation with isomeric structures and distinct photocatalytic properties.
CRIS-Team Scopus Importer:2023-03-20